2011
DOI: 10.1590/s1516-05722011000400001
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do extrato aquoso de cabelo de milho (Zea mays L.) sobre a excreção renal de água e eletrólitos e pressão arterial em ratos Wistar anestesiados

Abstract: RESUMO:O milho (Zea mays L.) possui nos estigmas (cabelo de milho) substâncias que o tornam diurético, podendo ser importante no controle da hipertensão. No presente estudo, foi investigado o efeito do extrato aquoso (EA) do cabelo de milho sobre o fluxo renal de água (V) e eletrólitos e a pressão arterial (PA) em ratos Wistar anestesiados. Foram realizados 3 grupos: I) Controle -administração intragástrica (AI) de 1mL de água destilada; II) AI de 1 mL de EA de cabelo de milho a 20% e III) AI de 1 mL de soluçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…[74] Likewise, another study measured the effects of water extract from CS on renal water flow, electrolyte and arterial pressure in anesthetized Wistar rats, and the results demonstrated that water extract from CS had a diuretic effect but did not result in loss of potassium or significant loss of sodium compared with control group supplemented with the diuretic. [75] Water extract of CS also exhibited significant anti-urolithic activity in vitro. [76] Moreover, the extracts of CS and parsley could be used as new functional food components with antioxidant and diuretic effects.…”
Section: Diuretic Effectmentioning
confidence: 92%
“…[74] Likewise, another study measured the effects of water extract from CS on renal water flow, electrolyte and arterial pressure in anesthetized Wistar rats, and the results demonstrated that water extract from CS had a diuretic effect but did not result in loss of potassium or significant loss of sodium compared with control group supplemented with the diuretic. [75] Water extract of CS also exhibited significant anti-urolithic activity in vitro. [76] Moreover, the extracts of CS and parsley could be used as new functional food components with antioxidant and diuretic effects.…”
Section: Diuretic Effectmentioning
confidence: 92%
“…A literatura descreve o uso de Quebra-pedra, Phyllanthus niruri, como terapia no controle de urolitíase e, destaca sua eficácia na prevenção de urólitos (Cruces, et al, 2013), já as espécies Cabelo de milho (Zea mays) e Uva ursi (Arctostaphylos uva-ursi) apresentam propriedades diuréticas (Pinheiro, et al, 2011;Das, 2020). Assim, os estudos apresentados confirmam as propriedades biológicas que justificam o uso tradicional dessas espécies.…”
Section: Folhas Flores E Rizomasunclassified
“…In China, corn silk has been reported to have the function of inducing diuresis (Wang & Zhao, 2019). Studies with Wistar rats have shown that the aqueous extract of corn silk has a diuretic effect, but does not act as a loop diuretic (diuretics that act at the ascending limb of the loop of Henle in the kidney) since it did not lead to potassium loss or marked sodium loss, compared to furosemide drug (Pinheiro et al, 2011). Also in China, people have been using corn Practical Application: This research investigated the antioxidant, antibacterial, photoprotective and cytotoxic properties of corn silk ethanol extract.…”
Section: Introductionmentioning
confidence: 99%